2016
DOI: 10.1088/0957-4484/27/14/145201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of doping on the far-infrared intersubband transitions in nonpolarm-plane GaN/AlGaN heterostructures

Abstract: This paper assesses the effects of Si doping on the properties of nonpolar m-plane GaN/AlGaN quantum wells (QWs) designed for intersubband (ISB) absorption in the far-infrared spectral range. For doping levels up to 3 × 10(12) cm(-2), structural analysis reveals uniform QWs with abrupt interfaces and no epitaxially induced defects. Cathodoluminescence spectroscopy confirms the homogeneity of the multiple QWs along the growth direction. Increasing the doping density in the QWs from 1 × 10(11) cm(-2) to 3 × 10(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
4
21
0
Order By: Relevance
“…To date, promising experimental results have been reported for near-and far-infrared intersubband absorption and photodetection in m-plane nitride heterostructures utilizing limited Al-composition alloys. [2][3][4][5][6][7][8][9][10][11][12] Mid-infrared intersubband absorption in m-plane AlGaN/GaN heterostructures grown by metal-organic chemical vapor deposition (MOCVD) was demonstrated by Kotani et al [4][5][6] We reported far-infrared (THz) intersubband absorption in AlGaN/GaN superlattices grown by molecular beam epitaxy (MBE). 2 Lim et al [7][8][9][10][11] also demonstrated short-to longwavelength infrared intersubband transitions in MBE-grown AlGaN/GaN heterostructures.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…To date, promising experimental results have been reported for near-and far-infrared intersubband absorption and photodetection in m-plane nitride heterostructures utilizing limited Al-composition alloys. [2][3][4][5][6][7][8][9][10][11][12] Mid-infrared intersubband absorption in m-plane AlGaN/GaN heterostructures grown by metal-organic chemical vapor deposition (MOCVD) was demonstrated by Kotani et al [4][5][6] We reported far-infrared (THz) intersubband absorption in AlGaN/GaN superlattices grown by molecular beam epitaxy (MBE). 2 Lim et al [7][8][9][10][11] also demonstrated short-to longwavelength infrared intersubband transitions in MBE-grown AlGaN/GaN heterostructures.…”
Section: Introductionmentioning
confidence: 98%
“…Nonpolar m-plane AlGaN/GaN heterostructures are interesting from both a fundamental material growth perspective and for practical applications in infrared optoelectronic devices. [1][2][3][4][5][6][7][8][9][10][11][12] Intersubband optoelectronic devices utilize optical transitions within the conduction band of GaN/AlGaN quantum wells to emit or detect infrared radiation. The accessible wavelength range is mainly determined by the conduction band-offset between the well and the barrier material, i.e., GaN and AlGaN in this case.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonpolar nitride heterostructures have been proposed as alternative materials to polar heterostructures for infrared intersubband (ISB) devices . Due to large conduction band offsets between GaN and AlGaN, and large longitudinal‐optical phonon energy, the nitrides are potential candidates for near‐ to far‐infrared lasers and photodetectors.…”
Section: Introductionmentioning
confidence: 99%
“…We have made significant progress in growing m‐plane GaN and m‐plane AlGaN/GaN superlattices with Al‐composition below 20% that enabled us to observe THz intersubband absorption . Others have also had success growing m‐plane Al(Ga)N/GaN superlattices by different techniques in certain composition ranges . However, it remains challenging to control the Al content of m‐plane AlGaN over the full compositional range.…”
Section: Introductionmentioning
confidence: 99%